Weathering the Storm: Asian Hedge Funds - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2010)
How has the financial crisis shaped the hedge fund industry in Asia? We survey the style, investment region, and assets under management landscape of Asia-based hedge funds before and after the recent economic downturn. Our findings suggest that during the early part of the crisis in 2007, macro and fixed income funds based in Australia were especially vulnerable. When Asian financial markets succumbed in 2008 and 2009, hedge fund exits ramped up in Singapore and Hong Kong, particularly amongst event driven and Japan-focused funds. Small funds were most susceptible to closure during the liquidity crunch. Conversely, CTAs and Greater China-focused funds appear to have weathered the stormy conditions relatively well.